Tidal Range and Sea Level Changes at The Area in front of Umm Qasr Port South of Iraq - Adel Jassim Al-Fartusi (مجلة جامعة الانبار للعلوم الصرفة, 2020)
The high maximum and low for sea level in north west of Arabian Gulf in the area next to Umm Qasr port were studied for a nodal lunar cycle that equal nineteen years (1999 – 2017). It was found that the sea level is rising. Depending on, the sea level monitoring of the nineteen years’ interval, the essential characteristics of Umm Qasr's tidal range have been identified. This study addressed the problems of the collective impact of tides and meteorological elements at sea level, more precise characterization is given to this phenomenon through defining the frequency division for the tidal sea level, where it was found that the prevailing range within the two values are (3.0 - 4.0m), while the actual average tide is (3.908m). In addition, was comparing the calculated and registered range of the tide through the study period was found that the recorded range exceeded the calculated range and this increase due to meteorological elements which increases the effectiveness in the summer months in the study area.